Pengaruh Campuran Spent Bleaching Earth (SBE) dan Semen Sebagai Bahan Stabilisasi Tanah Lempung Terhadap Nilai California Bearing Ratio (CBR): The Influence of Spent Bleaching Earth (SBE) and Cement Mixture as Clay Soil Stabilization Material on California Bearing Ratio (CBR) Value - Alwiyah, Sarah; Anggreana, Vella; Mildawati, Roza (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2024)
One method for enhancing the natural state of the soil is soil stabilization. Spent bleaching earth (SBE) is the solid waste left over after palm oil is refined for use in oleochemical industry processes. When the field test value exceeds 3% and the laboratory test value exceeds 6%, the soil strength is deemed favorable. The test results indicate that as the curing time increased, the natural soil's California Bearing Ratio (CBR) value increased as well. After 0 days of curing, the natural soil's CBR value was 11.91%; after 4 days, it rose to 12.59%; and after 7 days, it reached 13.99%. Furthermore, the soil that underwent a 4-day soak had a CBR value of 4.01%. Concurrently, the CBR value increased with increasing curing time in the mixed soil CBR test, which had a composition of 10% cement and 22.5% SBE. The mixed soil's CBR value at 0 days of curing was 12.66%. Nevertheless, the CBR value increased significantly to 22.64% after 4 days of curing. Furthermore, the CBR value increased to 27.11% after 7 days of curing. The mixed soil's CBR value was 23.52% over the course of the four-day soaking period. We can conclude that the natural soil and the mixed soil exhibit their highest CBR values following a 7-day curing period. This suggests that the CBR value is influenced by the curing time. In both soil types, a higher CBR value was noted with longer curing times.